2020
DOI: 10.3390/ijms21083006
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic Profiling of Circular RNA in Different Brain Regions of Parkinson’s Disease in a Mouse Model

Abstract: Parkinson’s disease (PD) is the second most common neurodegenerative disease and although many studies have been done on this disease, the underlying mechanisms are still poorly understood and further studies are warranted. Therefore, this study identified circRNA expression profiles in the cerebral cortex (CC), hippocampus (HP), striatum (ST), and cerebellum (CB) regions of the 1-methyl-1,2,3,6-tetrahydropyridine (MPTP)-induced PD mouse model using RNA sequencing (RNA-seq), and differentially expressed circRN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 57 publications
0
40
0
Order By: Relevance
“…Further, a circRNA transcriptome profiling study from different brain regions of MPTP-induced PD mouse model revealed differential expression of six circRNAs predicted to be involved in the PD-related pathways. Through an in silico analysis, mmu-circRNA-0003292, and mmu_circRNA_0001320 were predicted to interact with well-known PD-related miRNAs, miR-132, and miR-124, respectively [150]. A recent study on RNA sequencing of brain samples from PD patients and controls also showed the presence of differentially expressed circRNAs in different brain regions.…”
Section: Circular Rnasmentioning
confidence: 98%
“…Further, a circRNA transcriptome profiling study from different brain regions of MPTP-induced PD mouse model revealed differential expression of six circRNAs predicted to be involved in the PD-related pathways. Through an in silico analysis, mmu-circRNA-0003292, and mmu_circRNA_0001320 were predicted to interact with well-known PD-related miRNAs, miR-132, and miR-124, respectively [150]. A recent study on RNA sequencing of brain samples from PD patients and controls also showed the presence of differentially expressed circRNAs in different brain regions.…”
Section: Circular Rnasmentioning
confidence: 98%
“…222,226,227 miR-132 regulates embryonic stem cell differentiation into dopaminergic cells, while miR-132 was upregulated in a PD mouse model and reduced dopamine neuron differentiation. The miRNA sponge mmu-circRNA-0003292 is hypothesized to sequester miR-132 and affect PD pathogenesis, 228 however, further experimental verification is needed.…”
Section: Mirna Therapeuticsmentioning
confidence: 99%
“…In addition, CircSLC8A1 expression was sensitive to OS status in culture cells, overall suggesting an OS-mediated deregulation of the CircSLC8A1/miR-128 pathway in PD. circRNAs have also been shown to be deregulated in multiple brain regions in the MPTP mouse model of PD [205]. The enrichment pathway analysis of deregulated circRNAs highlighted diverse biological functions, including synapse function, neuronal differentiation, axon guidance and PD metabolism.…”
Section: Parkinson's Diseasementioning
confidence: 99%
“…The enrichment pathway analysis of deregulated circRNAs highlighted diverse biological functions, including synapse function, neuronal differentiation, axon guidance and PD metabolism. Specifically, the authors suggest that the mmu_circRNA_0003292-miRNA-132-Nr4a2 pathway can be involved in the regulation of pathogenic mechanisms [205]. Using the same mouse model of PD, a recent report has shown a decreased expression of circDLGAP4 upon MPTP treatment and an analogous deregulation pattern in MPP+ treated cell models [206].…”
Section: Parkinson's Diseasementioning
confidence: 99%